OSTE+ for in situ SAXS analysis with droplet microfluidic devices. Issue 16 (22nd July 2020) - Lange, Tobias; Charton, Sophie; Bizien, Thomas; Testard, Fabienne; Malloggi, Florent
Abstract : Thin full OSTE+ chip fabrication and characterization for in situ SAXS studies. Abstract : In recent years, microfluidic-based sample preparation techniques have emerged as a powerful tool for measurements at large scale X-ray facilities. Most often the microfluidic device was a form of hybrid system, i.e. an assembly of different materials, because a simple, versatile and inexpensive microfabrication method, on the one hand, and X-ray compatibility, on the other hand, cannot generally be achieved by the same material. The arrival of a new polymer family based on off-stoichiometric thiol-ene-epoxy (OSTE+) has recently redistributed the cards. In this context, we studied the relevance and the compatibility of OSTE+ for small-angle X-ray scattering (SAXS) studies. The material was characterized regarding its X-ray properties (transmission coefficient, attenuation coefficient, scattering pattern and polymer aging under X-ray light) and their comparison with those of the usual polymers used in microfluidics and/or for synchrotron radiation experiments. We show that OSTE+ has a better SAXS signal than polyimide, the polymer of reference in the SAXS community. Then a detailed protocol to manufacture a suitably thin full OSTE+ chip (total thickness <500 μm) is described and the potency of full OSTE+ devices for in situ SAXS studies is highlighted in two case-studies: the characterization of gold nanoparticles and the precipitation of cerium oxalate particles, both in moving droplets. Additionally, a method to analyze the scattering signals from droplet and carrier phase in a segmented flow is proposed.